Development of INTERACTIVE MEDIA IN SCIENCE LEARNING ON HUMAN DIGESTIVE SYSTEM MATERIAL FOR JUNIOR HIGH SCHOOL STUDENT GRADE 8TH - Rachma Deli Fachrin; Latisma Dj (Universe, 2021)
This study aims to develop interactive media on the digestive system material and then find out its validity and practicality. This type of research is development research is development using modified 4-D models, consisting of 4 stage namely, define, design, develop and disseminate. But at the disseminate stage is not done. The define phase consist of initial-end analysis, student analysis and media analysis. At the design stage, interactive media design is carried out. At the develop stage, the validity test was conducted by the validator, namely the lecturer of Natural Science, Faculty of Mathematic and Natural Science, UNP, and the practicality test by thr science teacher of SMP N 6 Padang and student of class VIII. Based on research that has been done, it’s obtained data for interactive media that has been made on the digestive system material can be used with valid categories by the validator and practical by the teacher and very practical by students, and can make the learning atmosphere more effective with media with media assistance learning in this form of interactive media.